Kecepatan Pengeringan, Penyusutan Dan Cacat-Cacat Pengeringan yang terjadi pada Pengeringan Kayu Paraserianthes Falcataria Secara Alami dan Dalam Dapur Pengering - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
Speed of drying, shrinkage and drying defects of 2 cm Paraserinthes falcataria Nielsen dried in air drying and in dry kiln are reported. Thirteen logs at diameter 30-50 cm were sawn live sawing, edged to the widest width and trimmed to 2.0 m length. The inner lumber (close to pith) were ripped into two boards due to the excessive split. The first half of the lumber from each log were stacked together and air dried and the other half of the lumber were kiln dried. Kiln schedule was set up according to. the COPCAL kiln mannual. In 51 days air drying, average moisture content of the lumber was 13,2%, while in the dry kiln after 8 days with effective drying treatment 53 hours, the average moisture content of the lumber was 9.56%. Shrinkage of the outer boards (close to bark) from green to their final moisture contents was averaged 8.50% and of the inner boards was averaged 11.60% in air drying. In the kiln drying, shrinkage of the outer boards was averaged 8.70% and of the inner boards was averaged 12.15%. End checks occured at small number of the outer boards at the length of about 17 cm. Almost no end check occured at the inner lumber. Length ening of old end checks were also found at small number of the lumber. Bowing occured at almost all of the lumber at 4.2 to 6.8 inm deflec tions. Crook occured at most of the lumber at 2.7 to 3.2 mm deflections